Effectiveness of Fentanyl in Facilitating Cannulation of Ampulla of Vater during Endoscopic Retrograde Cholangiopancreatography - Pun, Ashis; Dhungana, Amit; Pariyar, Jewan; Upadhyay, Hari Prasad (Journal of Nepal Health Research Council, 2021)
Background: Endoscopic retrograde cholangiopancreatography is carried out under moderate sedation mostly by use of propofol, opioids and benzodizepines. The aim of study is to assess difficulty in cannulation of ampulla of vater with the use of fentanyl. Methods: A prospective randomized double blind comparative study was conducted at Bharatpur Hospital from August 2019 to August 2020 among patients undergoing Endoscopic retrograde cholangiopancreatography. Total 100 patients were enrolled in study and were divided in two groups – Group P (propofol and midazolam) and Group FP (propofol, midazolam and fentanyl). Ease of cannulation was determined using Freeman scale. Independent sample t-test was used to compare mean between two groups and Chi Square test was used to compare categorical variables. Results: Mean age (51.36±17.750 years versus 56.74±16.995 years), weight (58.88±8.151 kg versus 57.32±8.431 kg) and gender distribution (14 versus 12 male patients and 36 versus 38 female patients) were comparable in both groups-Group P and Group FP. There were 34 patients in Group P and 37 patients in Group FP with easy cannulation and 16 patients in Group P and 13 patients in Group FP with difficult cannulation, which was comparable (p value=0.509) Conclusions: Cannulation of ampulla of vater is not affected by the use of fentanyl in combination with propofol when compared to propofol alone and can be routinely used during endoscopic retrograde cholangiopancreatography. Keywords: Ampulla of vater; endoscopic retrograde cholangiopancreatography; fentanyl; propofol